Hydroxyapatite coatings on magnesium based biomaterials - Başlayıcı, Serkan (İdris Karagöz, 2021)
Biomaterials can be coated with hydroxyapatite for different purpose. These reasons can be listed as increasing corrosion resistance, increasing biocompatibility, increasing adhesion to bone or tissue etc. Since the use of magnesium-based biomaterials is generally based on biodegradability properties, one of the main tasks of hydroxyapatite coating will be to increase corrosion resistance. In this study, hydroxyapatite coating methods on Mg based biomaterials and methods used to determine corrosion rate are mentioned. These methods are plasma spray coating, electrostatic coating, pulse electroplating, electrophoretic coating, sol-gel deposition, radio frequency magnetron sputtering. As a coating method, especially plasma spray coating is a promising method. The main reason for this is that there is no need for a secondary heat treatment after coating and that homogeneous coatings are obtained.
Keywords: Material Production Technologies; Malzeme Üretim Teknolojileri